O surgimento da Coordenação Nacional de Lutas Sociais (CONLUTAS) frente ao processo de resistências e adaptações do movimento sindical no Brasil à lógica do capital - Guimarães Júnior, Mário Costa de Paiva (2016)
This research aims to study the conditions of organization of workers in Brazil, from 2003 to 2008. For this, the focus of the analysis will be centered on the National Coordination of Struggles (CONLUTAS). It is an entity that emerged in March 2004, in a meeting in Luziânia-GO, with about 1800 activists from 279 unions from all over Brazil dissatisfied with the political and practical positions of the trade union centrals in Brazil, including among them the Central Única dos Trabalhadores (CUT) as the country's largest Trade Union in that period and to this day. I will address some objective and subjective dimensions of this issue, related to political, social, economic and cultural aspects, taking into account the process of productive restructuring of capital that has occurred in the country in recent decades. The research deals with the consequences for the trade union movement in relation to the process of approximation and linkage to the State, the hegemony of the practice of citizen unionism and the relationship with the victory of Luiz Inácio Lula da Silva and PT in the 2002 presidential elections. CONLUTAS 'trajectory, which is part of a new scenario of reorganization of the workers movement in Brazil, to verify whether or not this initiative is something unprecedented in terms of the organization of workers in Brazil. The work analyses points out the potentialities, limitations and contradictions of the political and organizational project proposed by CONLUTAS.